Endovascular stroke treatment today - Grunwald, Iris Q.; Wakhloo, A. K.; Walter, S.; Molyneux, A. J.; Byrne, J. V.; Nagel, Simon; Kühn, A. L.; Papadakis, M.; Fassbender, K.; Balami, J. S.; Roffi, M.; Sievert, H.; et al. (American journal of neuroradiology, 2011)
SUMMARY: The purpose of this study was to review current treatment options in acute ischemic stroke, focusing on the latest advances in the field of mechanical recanalization. These devices recently made available for endovascular intracranial thrombectomy show great potential in acute stroke treatments. Compelling evidence of their recanalization efficacy comes from current mechanical embolectomy trials. In addition to allowing an extension of the therapeutic time window, mechanical recanalization devices can be used without adjuvant thrombolytic therapy, thus diminishing the intracranial bleeding risk. Therefore, these devices are particularly suitable in patients in whom thrombolytic therapy is contraindicated. IV and IA thrombolysis and bridging therapy are viable options in acute stroke treatment. Mechanical recanalization devices can potentially have a clinically relevant impact in the interventional treatment of stroke, but at the present time, a randomized study would be beneficial.